Phosphatase PP2A promotes RTA dephosphorylation to impair KSHV lytic replication - Bai, Lei; Dong, Lianghui; Dong, Jiazhen; Liang, Xiaowei; Peng, Jiangwei; Chen, Yuncai; Sun, Xiaoyi; Chen, Yuting; Li, Xintong; Cai, Hua; Huang, Jing; Cao, Zixu; et al. (PLOS Pathogens, 2025)
Kaposi’s Sarcoma-associated herpesvirus (KSHV) is a human γ herpesvirus that establishes two different phases in its life cycle, the latency and lytic replication. KSHV-encoded replication and transcription activator (RTA), an immediate-early master switch protein, plays a central role in switching the viral latency to lytic replication. Extensive studies have described the mechanisms that RTA functions as a transcription factor to activate its downstream viral genes expression, initiating lytic replication. Phosphorylation of RTA has been shown to be critical for its function, but the regulatory mechanisms of phosphorylation and dephosphorylation of RTA have not been fully elucidated. In this study, we showed that RTA interacts with the scaffold protein PPP2R1A of phosphatase PP2A. We next demonstrated that PPP2R1A overexpression and a pharmacological agonist of PP2A, forskolin, both inhibit viral genes expression and impair the production of KSHV progeny virions during viral lytic replication. The underlying mechanism involves RTA dephosphorylation mediated by phosphatase PP2A, which impaired the transcription activity of RTA and therefore suppressed KSHV lytic replication. Interestingly, to evade this host antiviral mechanism, KSHV RTA can promote PPP2R1A degradation through ubiquitin-proteasome pathway. Taken together, we identified that the scaffold protein PPP2R1A is a new binding partner of RTA, and the interaction induces RTA dephosphorylation mediated by phosphatase PP2A, impairing KSHV lytic replication, which provide new insights into the development of novel antiviral strategies.